PENGARUH STRATEGI PEMASARAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING: Case Study On OVO Digital Payment In Bandung City - Panjaitan, Dertaida; Setyorini, Retno (JURISMA : Jurnal Riset Bisnis & Manajemen, 2020)
This research was conducted to determine the effect of marketing strategies on customer loyalty through customer satisfaction on digital payment OVO in Bandung. Among them are complaints about OVO application errors, handling problems that are not responded quickly by the parties concerned, points that cannot be used by users and other problems that affect OVO users. The research method used is quantitative method with the type of research is causal descriptive, the measurement scale used is the Likert scale. Data analysis method used in this study is Structural Equation Modeling. Data processing is performed using SmartPLS. The results of the study indicate that the marketing strategy influences the customer loyalty through customer satisfaction as an intervening variable in OVO digital payment in the city of Bandung. This is due to the two structural variables that influence significantly on customer loyalty. Keywords: marketing strategy, customer satisfaction, customer loyalty